2017
DOI: 10.1002/adma.201703119
|View full text |Cite
|
Sign up to set email alerts
|

Polyhedral 30‐Faceted BiVO4 Microcrystals Predominantly Enclosed by High‐Index Planes Promoting Photocatalytic Water‐Splitting Activity

Abstract: High-index crystal facets, denoted by a set of Miller indices {hkl} with at least one index greater than unity, possess a high density of low-coordinated atoms, steps, edges, and kinks that serve as highly active catalytic sites. [1][2][3] High-index surfaces normally grow faster than lowindex ones and are usually lost during crystal growth due to minimization of the total surface energy. Although the selective exposure of high-index facets at the surface is an important and challenging research topic, much pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
112
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 174 publications
(119 citation statements)
references
References 46 publications
2
112
0
1
Order By: Relevance
“…Recently, Li et al . synthesized 30‐faceted BiVO 4 polyhedra mainly exposed by {321}, {132} and {121} facets, which exhibits a 3–5 times enhancement in the activity of OER compared with the single crystals exposed with low‐index facets . GGA‐PBE calculations revealed that water decomposition is easier on these high‐index surfaces than on low‐index surfaces, e. g. (010), (110), and (101), and the predicted overpotentials for OER on high‐index surfaces are smaller than those on low‐index surface by 0.77∼1.14 V. Sun et al .…”
Section: Controlling Crystal Morphologymentioning
confidence: 99%
“…Recently, Li et al . synthesized 30‐faceted BiVO 4 polyhedra mainly exposed by {321}, {132} and {121} facets, which exhibits a 3–5 times enhancement in the activity of OER compared with the single crystals exposed with low‐index facets . GGA‐PBE calculations revealed that water decomposition is easier on these high‐index surfaces than on low‐index surfaces, e. g. (010), (110), and (101), and the predicted overpotentials for OER on high‐index surfaces are smaller than those on low‐index surface by 0.77∼1.14 V. Sun et al .…”
Section: Controlling Crystal Morphologymentioning
confidence: 99%
“…Thesamples prepared for 10 h, 50 h, 100 h, and 200 h are denoted as BiOCl-10, BiOCl-50, BiOCl-100, and BiOCl-200, respectively.S EM images show that BiOCl-10 presents regular square-plate morphology with size of approximately 3 mm ( Figure 1a and Figure S1). With the increase of reaction time,t he plates grow gradually thicker (Figure 1b [6] With further extending the reaction time to 200 h, it can be observed that the growth of BiOCl crystals was slow,and the change in facet composition of BiOCl is not obvious (BiOCl-200, Figure 1d). Thec orresponding schemes of BiOCl prepared under different time give an intuitive guide for illustrating the morphology change.The growth the eighteenfaceted BiOCl crystal seems to be spontaneous.The presence of new facets with prolonged hydrothermal treating time is similar to that observed for BiVO 4 .…”
mentioning
confidence: 99%
“…With the increase of reaction time,t he plates grow gradually thicker (Figure 1b [6] With further extending the reaction time to 200 h, it can be observed that the growth of BiOCl crystals was slow,and the change in facet composition of BiOCl is not obvious (BiOCl-200, Figure 1d). [6,9] Tr ansmission electron microscopy (TEM) verifies the regular square plate morphology of BiOCl-10 with four sharp corners ( Figure 1e). [6,9] Tr ansmission electron microscopy (TEM) verifies the regular square plate morphology of BiOCl-10 with four sharp corners ( Figure 1e).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…BiVO 4 has an appropriate VB edge (≈2.4 eV versus NHE) and attracts strong attentions as one of the most promising photocatalysts for water oxidation under visible light. 30‐faceted BiVO 4 polyhedra mainly exposed by {321}, {132}, and {121} high‐index facets are synthesized by Zou et al . The high‐index facets exposed BiVO 4 caused a 3–5 times improvement of oxygen production, and the apparent quantum efficiency (AQE) of O 2 generation achieves 18.3 % under irradiation of 430 nm light.…”
Section: Facet Engineering On Bismuth‐based Photocatalytic Materialsmentioning
confidence: 99%